Application design of catfish species specification - Yanto A.F.; Nguyen P.T.; Laxmi Lydia E.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The system is a program inside of the computer and the task is to complete specific need or task. In its development, the system program has been developed for various fields, for example in determining the specification of catfish species. Catfish is a type of fish that live in fresh water. Catfish is easily recognized because their body is slippery, slightly flat elongated, and has long "mustache" that sticks out from around the mouth. Therefore, the researchers wrote this paper to improve service for the society and to facilitate the community in determining the type of catfish. BEIESP.